The effects of despeckling filters on pore size measurements in collagen scaffold micro‐CT data. (13th August 2021) - Meek, Matt C.; Best, Serena; Cameron, Ruth
Summary: Micro‐CT is often used to assess the characteristics of porous structures such as tissue engineering scaffolds and trabecular bone. Prior to analysis, micro‐CT images can be thresholded and filtered to remove noise. Scaffold pore size affects mechanical properties and biological cell behaviour and is a frequently assessed parameter. This paper identifies and characterizes an artefact affecting a commonly used filter which erroneously increases mean pore size. The 3D sweep despeckling filter removes all but the largest object within a volume of interest, and therefore deletes any disconnected objects located at the periphery, increasing measured mean pore size. This artefact is characterized, and effective methods to mitigate its effects are devised, involving despeckling a sufficiently large volume of interest, then reducing the volume of interest in size to remove the error prior to analysis. Techniques to effectively apply this method to other data sets are described. This method eliminates the artefact but is time‐consuming and computationally expensive. Alternative, more economical filters which remove objects below a specified size are also assessed but are shown to be affected by the same artefact. These results will help to guide the implementation of future studies investigating the effects of pore size. Lay Description: Micro‐CT is an imaging technique commonly used to assess the characteristics of porous structures, such as medical tissue engineering scaffolds and bone. Prior to analysis micro‐CT images are often processed by thresholding and filtering to improve the image quality. Scaffold pore size affects biological cell behaviour and mechanical properties, and is a frequently assessed parameter when evaluating medical scaffolds. This paper identifies and characterises an artefact affecting a commonly used filter which erroneously increases measured peripheral mean pore size. The artefact affects the periphery of volumes of interest which have been filtered by a technique called 3D sweep despeckling. This filter removes all but the largest object in the volume of interest, and therefore also deletes small disconnected objects located at the volume of interest periphery. This paper characterises the artefact, and effective methods to mitigate its effects are devised, involving despeckling a sufficiently large volume of interest, then reducing the volume of interest in size to remove the error prior to analysis. Techniques to ascertain the parameters required to effectively apply this artefact reduction method to other datasets are described. This method eliminates the artefact, but is time consuming and computationally expensive. Alternative, more economical despeckling filters are assessed for their ability to remove the error. Of these, a filter which deletes objects below a prescribed area was found to be most effective when performing 2D pore analysis on scaffolds, and the same filter applied to objects below a set volume was best when 3D pore analysis was used. This filter was found to be afflicted by the same artefact as sweep despeckling. These results will help guide the implementation of future studies investigating the effects of pore size.